(untitled) (Journal of the College of Basic Education, 2026)
Intonation is strongly linked to grammatical styles through the declarative and imperative moods, as it plays an important role in determining grammatical meanings through grammatical styles such as interrogation, exclamation, command, prohibition, supplication, and conveying information through nominal and verbal sentences (subject and predicate) and emphasizing them with particles, fronting, backshifting, oaths, and so on. Each of these types has a specific tone. The ascending tone is represented by the interrogative particle "hal" and the interrogative particle "hamza," and the descending tone is exemplified by supplication, lament, and reproach. There is also the moderate tone, in which the speech is steady, indicating wisdom and truth, and is often found in declarative sentences. Intonation is also related to the context and situation.